Football training vs. martial arts training: How are they related to executive function skills in 5–6-year-old boys? - Yakushina, Anastasia; Rudnova, Natalia; Dmitrieva, Maria; Pashenko, Aleksander; Chichinina, Elena (Frontiers in Psychology, 2025)
Sports training is one of the most popular extracurricular activities among preschool and elementary school children. The aim of this pilot study was to compare executive function skills in preschool boys who participated in football training and those who undertook martial arts training. The participants were sixty (60) typically developing 5–6-year-old boys from large Russian cities. There were two groups with 30 boys in each group: a football group and a martial arts group. Inclusion criteria were as follows: (a) male gender; (b) boys did not attend any extracurricular activities other than their football training or martial arts training; (c) the duration of football or martial arts training session was more than 30 min; (d) boys attended these trainings for at least 6 months and no more than 2 years. Caregivers reported on the specifics of child’s attendance at sports training and child’s age, maternal education, and family income, which were used as control variables. The results indicated that boys involved in football training had significantly higher spatial component of visuospatial working memory compared to boys involved in martial arts training. Taken together, these findings suggest that football training compared to martial arts training in 5–6-year-old boys may have more potential in terms of developing spatial component of visuospatial working memory. The results of this pilot study could serve as a basis for further investigation on this topic.